Effects of Diamond and Carbide Burs on Dentin Bond Strengths of Self - Etch Bonding Systems - Azita Kaviani; Asadollah Ahmadzadeh; Jafar Shahroie; Zahra Ghasemi (Islamic Dental Association of Iran, 2013)
Bachground and Aim: Nowadays, with regard to the quantitative and qualitative development of dental esthetic services and qualitative advances made in tooth-colored restorations, there is a great rise of demands for use of composite resins. The aim of this study was to assess the efficiency of diamond and carbide burs on bond strength of a self-etch adhesive to dentin .   Materials and Methods: In this in vitro experimental study sixty sound extracted human third molars were mounted in self cure acrylic resin. The teeth were randomly assigned to two groups (n=30 each). In the first group, the teeth were ground with high-speed medium grit diamond bur and in the second group the teeth were ground with high-speed carbide burs. A composite cylinder with a 3 mm diameter was bonded to each specimen with a self-etch adhesive system and the shear bond test was performed using a universal testing machine. The results were expressed in MPas and were subjected to and Tukey's test .   Results: The mean shear bond strength in diamond and carbide burs were 17.67 MPa (SD= ±4.41) and 14.51 MPa (SD= ±5.18), respectively. There was a significant difference in dentin bond strength between two groups. (P< 0.05) .   Conclusion: The use of different burs affect the shear bond strength of the self-etch adhesives to dentin. This adhesive performed significantly better when a diamond bur was used to prepared dentin surface .